P224 Deconstructing distress: Stakeholder engagement for evidence-based, patient-centered interventions for the management of IBD-associated psychological distress. (21st January 2022) - Heisler, C G; Rohatinsky, N; Stewart, M; Vallis, M; Shepherd, T; Wozney, L; Cassidy, C; Currie, B; Phalen-Kelly, K; Robar, J; Targownik, L; Huard, T; et al.
Abstract: Background: The growing prevalence of Inflammatory Bowel Disease (IBD) along with increasing complexity of providing high-quality, patient-centered care within a resource-constrained healthcare environment presents a major challenge. IBD-related psychological distress (IBD-PD) is the emotional impact of IBD and is associated with mental health disorders, increased disease severity, and premature mortality. With estimates of nearly 90% of IBD patients experiencing PD, the inability to provide high-quality, person- centered care for IBD- PD that is proportionate to clinical need is a significant care gap in the Canadian healthcare system. The aim of this project was to generate stakeholder-derived data to inform the design and development of stepped-intensity, cognitive behavioral therapy-based interventions for IBD-PD using evidence-based, patient–centered interventions and implementation strategies. Methods: Virtual semi-structured interviews were conducted from September to October 2021. The interview guide was developed iteratively by researchers, IBD care providers, and patient research partners and guided by the COM-B Model of Behaviour and the Theoretical Domains Framework. Interview questions assessed perceptions, experiences, barriers, and facilitators to accessing IBD-PD care. Adults diagnosed with IBD were recruited from academic centers across Canada. Interviews were co-facilitated by a researcher and patient research partner, audio recorded, and transcribed. Using thematic analysis, codes were generated to identify themes using an inductive approach. Results: As of October 2021, eleven interviews have been completed, with data collection ongoing. The mean participant age was 33.5 years (range 21–55 years) with 63.6% of respondents identified as female (7/11). The majority of participants worked full time (8/11, 72.7%) and all had completed at least high school. Diagnoses of Crohn's Disease (7/11, 63.6%) were more common than ulcerative colitis (4/11, 36.4%) among the participants. Thematic analyses identified five major themes: 1) Lack of holistic care and acknowledgement of IBD-PD; 2) System-level and financial barriers to psychological support; 3) Lack of psychological support from providers with an understanding of IBD; 4) Preference for individualized virtual-based support; 5) Heavy reliance on informal support structures (caregivers) due to lack of access to formal psychological support. Conclusion: As part of human-centered design, stakeholder engagement is key to understanding behavioral, social, attitudinal, and environmental barriers and facilitators for accessing IBD-PD care. Interviews are ongoing and specific intervention functions will be defined and incorporated into patient-centered implementation strategies.